Measurement of WZ and ZZ production in pp collisions at [Formula: see text] in final states with b-tagged jets - CMS Collaboration; Chatrchyan, S; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; et al. (The European physical journal. C, Particles and fields, 2014)
Measurements are reported of the WZ and ZZ production cross sections in proton-proton collisions at [Formula: see text][Formula: see text] in final states where one Z boson decays to b-tagged jets. The other gauge boson, either W or Z, is detected through its leptonic decay (either [Formula: see text], [Formula: see text] or [Formula: see text], [Formula: see text], or [Formula: see text]). The results are based on data corresponding to an integrated luminosity of 18.9 fb[Formula: see text] collected with the CMS detector at the Large Hadron Collider. The measured cross sections, [Formula: see text] and [Formula: see text], are consistent with next-to-leading order quantum chromodynamics calculations.